2014
DOI: 10.1016/j.devcel.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved Misshapen-Warts-Yorkie Pathway Acts in Enteroblasts to Regulate Intestinal Stem Cells in Drosophila

Abstract: SUMMARY Similar to the mammalian intestine, the Drosophila adult midgut has resident stem cells that support growth and regeneration. How the niche regulates intestinal stem cell activity in both mammals and flies is not well understood. Here we show that the conserved germinal center protein kinase Misshapen restricts intestinal stem cell division by repressing the expression of the JAK-STAT pathway ligand Upd3 in differentiating enteroblasts. Misshapen, a distant relative to the prototypic Warts activating k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(151 citation statements)
references
References 74 publications
4
146
1
Order By: Relevance
“…Animals were maintained under conditions of a 12-h-light/12-h-dark cycle and fed standard chow (LabDiet 5P76) unless otherwise stated. Mice with conditional Map4k4 floxed alleles were generated as described elsewhere (11) and were backcrossed to C57BL/6J mice for at least 7 generations. To inactivate Map4k4 in adult mice, homozygous Map4k4 flox/flox animals were crossed to B6.CgTg(UBC-cre/ERT2)1Ejb/J mice (Jackson Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…Animals were maintained under conditions of a 12-h-light/12-h-dark cycle and fed standard chow (LabDiet 5P76) unless otherwise stated. Mice with conditional Map4k4 floxed alleles were generated as described elsewhere (11) and were backcrossed to C57BL/6J mice for at least 7 generations. To inactivate Map4k4 in adult mice, homozygous Map4k4 flox/flox animals were crossed to B6.CgTg(UBC-cre/ERT2)1Ejb/J mice (Jackson Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…Phosphorylation of Wts by Hpo also requires adaptor proteins such as Mats and Merlin (Mer) to recruit Wts to the plasma membrane Yin et al 2013). Recent studies show that two other kinases, Misshapen (Msn) and Happyhour (Hppy), can activate Wts and repress Yki independently of Hpo (Li et al 2014a;Zheng et al 2015). There is evidence that, like Hpo, Hppy also phosphorylates the hydrophobic motif of Wts ).…”
Section: Core Components Of the Mammalian Hippo Pathwaymentioning
confidence: 99%
“…We and others have recently reported that MST1/2 and MAP4Ks act in parallel to phosphorylate and activate LATS1/2, and deletion of both MST1/2 and MAP4Ks is required to abolish LATS1/2 hydrophobic motif phosphorylation and activation (Li et al 2014a;Meng et al 2015;Zheng et al 2015). Regulation of MST1/2 kinase activity has been extensively studied.…”
Section: The Regulation Of Lats-activating Kinases Mst1/2 and Map4ksmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also conceivable, that alterations in this regulation in the context of aberrant MAP4K4 activation could result in developmental defects in the embryo and cancer initiation/ progression in the adult organism. In addition to its role in the developing organ, MAP4K4 also contributes to reshaping the adult organism, where it restricts differentiation of myoblasts into myotubes [40] or in enteroblasts, where it controls differentiation by phosphorylation of the Hippo pathway core component LATS1/2 and concomitant degradation of the transcriptional regulators YAP/TAZ [41].…”
Section: Development and Differentiationmentioning
confidence: 99%